Los activos biológicos en la estructura contable y financiera en las PYMES del sector agrícola ecuatoriano - Celi Jaya, Teresa Janeth (2019)
The study of biological assets in the accounting and financial structure in the SMEs of the Ecuadorian agricultural sector was developed from a field approach where it shows the results obtained from the collection of information from the poultry companies of Bucay Canton, regarding to its administrative, financial - accounting and operational structure using field research to the total of the sample, through the instruments of the survey, the interview and the analysis of financial status model through work papers. This research investigated the need for these companies to establish and consolidate their aforementioned structures in order to improve productive management, in order to move towards business development. For the investigation it was necessary to determine the main theoretical bases on the productive process, the infrastructure and the inputs and main materials that are used within the aviculture…....